Pengaruh Budaya Organisasi, Kerjasama Tim, Dan Gaya Kepemimpinan Terhadap Kinerja Pegawai (Studi Pada Kantor Badan Pusat Statistik Kabupaten Probolinggo) (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine how the influence of organizational culture, teamwork, and leadership style on employee performance at the Central Statistics Agency office of Probolinggo Regency. The sample in this study were all employees of the Central Statistics Agency of Probolinggo Regency, totaling 36 people. This data collection method uses a questionnaire distribution method. This data analysis technique uses multiple linear regression analysis technique with SPSS tool. The results showed that simultaneously organizational culture, teamwork, and leadership style had a significant effect. Partially, organizational culture has no significant effect on employee performance. And partially Teamwork and leadership style affect employee performance. Keywords : Organizational Culture, Teamwork, Leadership Style, Employee Performance